1982
DOI: 10.7589/0090-3558-18.1.59
|View full text |Cite
|
Sign up to set email alerts
|

HELMINTHS OF THE SPOTTED SEAL, Phoca largha, FROM THE BERING SEA

Abstract: Fifty-five spotted seals, Phoca largha, from the seasonal pack ice of the Bering Sea were examined for helminth parasites. Twelve species of helminths were found: Anophryocephalus ochotensis, Diplogonoporus tetrapterus, Diphyllobothrium cordatum, Phocanema decipiens, Contracaecum osculatum, Dipetalonema spirocauda, Phocitrema fusiforme, Corynosoma semerme, C. strumosum, C. validum, C. villosum, and Bolbosoma sp. Six species are new host records (A. ochotensis, D. tetrapterus, D. cordatum, D. spirocauda, C. val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 2 publications
2
9
0
1
Order By: Relevance
“…Corynosoma obtuscens was described in California sea lions (Zalophus californianus) from the California coast Table 2 Prevalence of hookworm (Uncinaria lucasi)-positive dead northern fur seal (Callorhinus ursinus) pups on St. Paul Island, Alaska periodically for over 50 years (Lyons et al , 2003 (Lincicome 1942) and also has been recorded in South American sea lions (Otaria byronia) (Tantaleán et al 2007). Corynosoma validum has been found in a bearded seal (Erignathus barbatus) and a walrus (Odobenus rosmarus) from St. Lawrence Island, AK (Van Cleave 1953) and has been recorded from seals from the Northern and Southern Hemisphere (Shults 1982). Dailey (1975) lists Corynosoma strumosum (=semerme), Cornynosma ventronudum, and Corynosoma villosum in northern fur seals.…”
Section: Discussionmentioning
confidence: 99%
“…Corynosoma obtuscens was described in California sea lions (Zalophus californianus) from the California coast Table 2 Prevalence of hookworm (Uncinaria lucasi)-positive dead northern fur seal (Callorhinus ursinus) pups on St. Paul Island, Alaska periodically for over 50 years (Lyons et al , 2003 (Lincicome 1942) and also has been recorded in South American sea lions (Otaria byronia) (Tantaleán et al 2007). Corynosoma validum has been found in a bearded seal (Erignathus barbatus) and a walrus (Odobenus rosmarus) from St. Lawrence Island, AK (Van Cleave 1953) and has been recorded from seals from the Northern and Southern Hemisphere (Shults 1982). Dailey (1975) lists Corynosoma strumosum (=semerme), Cornynosma ventronudum, and Corynosoma villosum in northern fur seals.…”
Section: Discussionmentioning
confidence: 99%
“…1904) Lühe, 1905 are the most widely distributed acanthocephalan species among oceanic seal populations (Dailey, 1975;Popov et al, 1980 ;Shults, 1982;Strauss et al, 1991: Measures & Gosselin, 1994. However, C. magdaleni (Montreuil, 1958) has rarely been reported.…”
Section: T Hree Corynosomamentioning
confidence: 99%
“…Corynosoma strumosum is also a widespread species in oceanic seals (Shults, 1982;Measures & Gosselin, 1994). However, this study shows that C. magdaleni is more prevalent than C. strumosum in the Bothnian Bay.…”
Section: T He Threementioning
confidence: 99%
“…Acanthocheilonema spirocauda has been located in the heart in most studies (Leidy 1858, Freund 1933, Anderson 1959, van den Broek & Wensvoort 1959, Menschel et al 1966, Helle & Blix 1973, Sweeney 1973, Lauckner 1985, Breuer et al 1988, Kennedy et al 1989, Skirnisson & Olafsson 1990, Lunneryd 1992, more specifically in the right ventricle (Anderson 1959, Brown et al 1960, Delamure & Treshchev 1966, MacDonald & Gilchrist 1969, Wipper 1974, Dunn & Wolke 1976b, Dailey 1978, Geraci 1978, Conlogue et al 1980, Eley 1981, Reijnders et al 1981, Shults 1982, van der Kamp 1987, Measures et al 1997, but it has also been found in the pulmonary artery (Anderson 1959, Delamure & Treshchev 1966, Menschel et al 1966, MacDonald & Gilchrist 1969, Dunn & Wolke 1976b, Stroud & Dailey 1978, Conlogue et al 1980, Eley 1981, Reijnders et al 1981, van der Kamp 1987, Measures et al 1997, in the vena cava caudalis (Borgesteede et al 1991), in the chorda tendineae and truncus pulmonalis …”
Section: Microhabitatmentioning
confidence: 99%
“…3). In addition, the heartworm occurs in hooded seals Cystophora cristata (Delamure & Treshchev 1966, Helle & Blix 1973, Pouvreau et al 1980, Measures et al 1997, bearded seals Erignathus barbatus (Popov 1975a, Eley 1981, ribbon seals P. fasciata (Popov 1975b, Eley 1981, Shults & Frost 1988, harp seals P. groenlandica (Measures et al 1997), ringed seals P. hispida (King 1964, Delamure & Popov 1974, Dailey 1975, Popov 1975a, Treshchev & Yurakhno 1975, Eley 1981, Measures & Gosselin 1994, Measures et al 1997 and spotted seals P. largha (Popov 1975a, Delamure et al 1976, Goltsev et al 1978, Eley 1981, Shults 1982. Perry (1967) described a related species to Acanthocheilonema (Dipetalonema) infecting California sea lions Zalophus californianus named Dipetalonema odendhali.…”
Section: Distribution and Host Rangementioning
confidence: 99%